PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI PENDEKATAN DEEP LEARNING PADA MATA PELAJARAN IPAS MATERI KEGIATAN EKONOMI KELAS VA SDN 35 PEKANBARU - Mariani, Yulita; Br Pasaribu, Martina; Alzura, Munira; Dewi Puspita, Sri; Cahyaningrum, Wuri; Witri, Gustimal; Dasrianti, Harni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low ability of deep learning of students in learning Natural and Social Sciences (IPAS) in class VA SDN 35 Pekanbaru. The purpose of this study was to improve the learning outcomes of students in the subject of Natural and Social Sciences (IPAS) through the application of a deep learning approach in class V SDN 35 Pekanbaru. This research is a class action research (PTK) which was carried out in two cycles with a subject of 24 students. Each cycle consisted of planning, implementation, observation, and reflection stages. The results showed a significant increase in the learning outcomes of students in each cycle. The average score of students increased from 74.6 to 80 in cycle 1 and continued to increase in cycle 2 to 94. Through this research, it can be seen that the deep learning approach is effective in improving concept understanding and active involvement of students in IPAS learning.